DEVELOPMENT OF THE MONITORING SOFTWARE AND BLOCKING OF UNAUTHORIZED PROCESSES IN THE AUTOMATED SYSTEMS - Петренко, А. Б.; Цьопич, А. В. (Science-based technologies, 2012)
The broad spectrum of threat in automatic system are realized because of running a lot of programs. In thiswork described the necessary of blocking such programs. For decision this problem created discretedelimetation access model according the HRU model. The delimetation of access based on white and black listsThis white and black lists contain the kit of resolved and prohibited programs for some user. Also described theway of monitoring and blocking unauthorized processes in automatic system according created lists. In the endwas offered a sample code to make such monitoring and blocking.